The effect of gnrh and simultaneous gnrh and pgf2α treatment of dairy cows with ovarian cysts - Hüseyin Erdem; Tevfik Tekeli; Mehmet Uçar; Mustafa Yenice (Eurasian Journal of Veterinary Sciences)
In this study, Ihe effects ol GnRH, and combination of GnRH and PGF2α hormones were investigated in the treatment ol ovarian cysts. Fourteen Holstein cows in postpartum having ovarian cysts on the days of 45-150 were selected by rectal palpation and ultrasonography from 270 Holstein cows. The cows with ovarian cysts were subjected to 2 rectal palpations 10 days apart. Following this ultrasonographic examinations were performed. In addılıon to these, plasma progesterone levels were also determined for detecting the effectiveness of treatment which would provide differential diagnosis of cysts at the time of injection day (0) and thereafter at days 3, 7 and 14. Fourteen cows with cystic ovaries were divided inlo two groups in equal numbers for the treatment. Twenty µg buserelin (GnRH) were injected to (he group I. and 20 jig buserelin (GnRH) and 25 mg dinoprost (PGF2α) to the group II 71.4 % of the cows were responded to the treatment and become pregnant in both groups. The time interval between the treatment-first estrous in the group I and II were 16.4+2.75 and 11.4+2.75 days (P>0 05), and the lime interval between the treatment-conception were 53+9.43 and 58.8±19.15 days (P>0.05), res-peciively. Average number of inseminations required per conception in both groups of animals was 1 4. As a result, Ihe present study suggests thai treatment of ovarian cysts with simultaneous GnRH and PGF2α were noi significant compared to GnRH alone based on Ihe findings of concerning about treatmenMirst estrous and treatment-conception intervals. It was found that simultaneous GnRH and PGF2α treatment had no effect lo alter the effects of each drug. In addition to these, determining the plasma progesteron levels was found useful for evaluation of the effectiveness ot the treatment.